Differentiated Teaching Module for Indonesian Language Based on Graphological Analysis of Letter I, R, G - Hamdani; Fitri Hartati; Novalina Setyaningrum (Indonesia Approach Education, 2023)
There are many ways that can be done to find out the individual characteristics of each student. The purpose of this study was to determine the internal potential of 10th Grade “Halimah” Students by using graphological analysis based on general characteristics, which is the slope of the writing direction, the slope of the writing lines, the spacing between words, and the spacing between lines, and based on the general characteristics, which are the letters